2020
DOI: 10.1109/access.2020.2978001
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Detection of Dispersed Defects in Resin Eyeglass Based on Machine Vision Technology

Abstract: This paper is concerned with detection of dispersed defects in the resin eyeglass. At present, manual detection is always used in industry, which inevitably causes impairing eyes and a high rate of false-negative detection. Statistics show that its average accuracy and the average detection time are about 85% and 10s, respectively. We for the first time propose an automatic approach to detection of dispersed defects in resin eyeglass, based on the machine vision technology. It is observed that the refractivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The two criteria are the real category and the category predicted by the classification model. The rows of the matrix symbolize the authentic values, and the columns of the matrix describe the predicted values [23,[28][29][30][31]. The confusion matrix analysis is shown in Table 3.…”
Section: Experiments Schemementioning
confidence: 99%
“…The two criteria are the real category and the category predicted by the classification model. The rows of the matrix symbolize the authentic values, and the columns of the matrix describe the predicted values [23,[28][29][30][31]. The confusion matrix analysis is shown in Table 3.…”
Section: Experiments Schemementioning
confidence: 99%
“…The rapid development of machine vision technology has provided a new solution for online defect detection and has achieved certain progress [1][2][3][4][5]. In the field of wafer inspection, scholars have proposed methods for different defect categories.…”
Section: Introductionmentioning
confidence: 99%
“…In the machine vision detection technology, they have high detection accuracy and high stability and are widely used in the field of surface feature measurement and defect detection [11,12]. Zhang et al [13], by analyzing the Si 3 N 4 ceramic balls' defect characteristics, found that some defects cannot be directly detected.…”
Section: Introductionmentioning
confidence: 99%